Antioxidant Effect of Curcumin on the Prevention of Oxidative Damage to the Cochlea in an Ototoxic Rat Model Based on Malondialdehyde Expression - Haryuna, Tengku Siti Hajar; Fauziah, Dyah; Anggraini, Sari; Harahap, M Pahala Hanafi; Harahap, Juliandi (International Archives of Otorhinolaryngology, 2021)
Introduction Aminoglycoside, as an antimicrobial medication, also has side-effects on the inner ears, bringing about hearing disorders. Curcumin has been proven to be a strong scavenger against various reactive oxygen species (ROS), and the increase in ROS production is considered to play an important role in the process of hearing disorder.Objective To prove that curcumin is an effective antioxidant to prevent cochlear damage based on malondialdehyde (MDA) expression.Methods The present research used 32 Rattus norvegicus, of the Wistar lineage, randomly divided into 8 groups: negative control, ototoxic control (a single dose of 40 mg/ml of gentamicin via intratympanic injection), 2 groups submitted to ototoxic control + curcumin treatment (100 mg/kg, 200 mg/kg), 2 groups who iunderwent ototoxic control + curcumin treatment for 7 days, and two groups submitted to curcumin treatment as prevention for 3 days + ototoxic induction.Results The results showed that the lowest dosage of curcumin (100 mg/kg) could decrease MDA expression on the cochlear fibroblastic wall of the ototoxic model; however using greater doses of curcumin (200 mg/kg) for 7 days would provide a better effect. Curcumin could also significantly decrease MDA expression when it was administered during the preototoxic exposure.Conclusion Curcumin can be used as a therapy for ototoxic prevention based on the decrease in MDA expression.
Keywords: curcumin; malondialdehyde; cochlear fibroblast; reactive oxygen species; ototoxicity; gentamicin